Marine Longilenes, Oxasqualenoids with Ser-Thr Protein Phosphatase 2A Inhibition Activity - Francisco Cen-Pacheco; Claudia Pérez Manríquez; María Luisa Souto; Manuel Norte; José Javier Fernández; Antonio Hernández Daranas (Marine Drugs, 2018)
The red seaweed Laurencia viridis is a rich source of oxygenated secondary metabolites that were derived from squalene. We report here the structures of three novel compounds, (+)-longilene peroxide (1), longilene (2), and (+)-prelongilene (3) that were isolated from this alga, in addition to other substances, 4 and 5, resulting from their acid-mediated degradation. The effect of compounds 1 and 3 against Ser-Thr protein phosphatase type 2A (PP2A) was evaluated, showing that (+)-longilene peroxide (1) inhibited PP2A (IC50 11.3 μM). In order to explain the interaction between PP2A and compounds 1 and 3, molecular docking simulations onto the PP2A enzyme-binding region were used.